Re-challenge Studies in Non-celiac Gluten Sensitivity: A Systematic Review and Meta-Analysis - Lionetti, Elena; Pulvirenti, Alfredo; Vallorani, Martina; Catassi, Giulia; Verma, Anil K.; Gatti, Simona; Catassi, Carlo (Frontiers in Physiology, 2017)
Background: Non-celiac gluten sensitivity (NCGS) is a syndrome characterized by intestinal and extra-intestinal symptoms related to the ingestion of gluten-containing food in subjects that are not affected by either celiac disease or wheat allergy. Since we still do not have validated biomarkers for the diagnosis of NCGS, the diagnostic protocol is based on the evidence of a clear-cut relationship between the ingestion of gluten (re-challenge) and clinical symptoms, after a remission during gluten-free diet. Several re-challenge studies have been published so far to evaluate the real prevalence of NCGS, reporting conflicting results. In this article we provide a meta-analysis and systematic review of the existing literature on re-challenge studies to evaluate prevalence figures of NCGS after re-challenge procedures. Methods: All clinical trials performing a gluten re-challenge with or without a placebo control in patients with a suspected diagnosis of NCGS were included. Search results were limited to studies published in English language. No publication date or publication status restrictions were imposed Results: Eleven studies were included in the meta-analysis. There was a considerable heterogeneity related to different sample size, type and amount of gluten administered, duration of challenge and different type of placebo. The overall pooled percentage of patients with a diagnosis of NCGS relapsing after a gluten challenge was 30%, ranging between 7% and 77%. The meta-analysis showed a not significant relative risk (RR) of relapse after gluten challenge as compared to placebo (RR: 0.4; 95% CI, -0.15 - 0.9; p=0.16). The overall pooled percentage of patients with a diagnosis of NCGS relapsing after a gluten challenge performed according to the recent Salerno criteria was significantly higher as compared to the percentage of patients relapsing after placebo (40% versus 24%; p=0.003), with a significant RR of relapse after gluten challenge as compared to placebo (RR: 2.8; 95% CI, 1.5 - 5.5; p=0.002). Conclusions: The prevalence of NCGS after gluten re-challenge is low, and the percentage of relapse after a gluten or a placebo challenge is similar. However, a higher number of patients will be correctly classified with NCGS if applying the recent Salerno criteria.